Lysosome targeted therapies in hematological malignancies - Manivannan, Madhumita S.; Peters, Anthea; Gibson, Spencer B. (Frontiers in Oncology, 2025)
Lysosomes are dynamic organelles integral to cellular homeostasis, secretory pathways, immune responses, and cell death regulation. In cancers, lysosomes become dysregulated to sustain proliferative signaling, metabolism, and invasion. In hematological malignancies such as acute myeloid leukemia (AML), acute lymphoblastic leukemia (ALL), chronic myeloid leukemia (CML), and chronic lymphocytic leukemia (CLL), leukemia cells demonstrate lysosome dysregulation with increased lysosomal activity, mTORC1 signaling, catabolic reactions, and autophagy. This supports the survival, metabolism, and proliferation of the leukemia cells. Lysosomes also play a critical role in treatment resistance by promoting cell survival and sequestration of drugs. This has led to the development of lysosome-targeted therapies such as cationic amphiphilic drugs (CAD), ATPase inhibitors or autophagy inhibitors to treat hematological malignancies. Lysosome-targeted treatments have shown effectiveness at inducing cell death by inhibiting cell survival mechanisms and inducing apoptosis. In addition, the combination of lysosome-targeted therapies with standard treatments gives synergistic apoptotic responses in leukemia cells. In this review, we will describe the lysosomal functions, their dysregulation in hematological malignancies and the development of lysosomal targeted therapies for leukemia treatment. By understanding lysosome dysregulation and developing lysosome-targeted agents, innovative treatment strategies could be effective in overcoming drug resistance in hematological malignancies.